Lift Shaft - Ghosh, Ayan (Jio Institute, 2023)
Frederick Stevens raised the height of BMC to 235 feet. At the rear of the tower, he made provision for a lift shaft, making it the first building in Mumbai to use a hydraulic lift. The water which was used in running the lift was stored between the outer and inner domes of the tower. The tanks had a capacity of 40,000 litres.